Regulatory Impacts of the Three Gorges Dam on Long-Term Terrestrial Water Storage Anomalies in the Three Gorges Reservoir Area: Insights from GRACE and Multi-Source Data - Yu Zhang; Yi Zhang; Sulan Liu; Xiaohui Wu; Yubin Liu; Yulong Zhong; Yunlong Wu (Remote Sensing)
Understanding the impact of human activities on regional water resources is essential for sustainable basin management. This study examines long-term terrestrial water storage anomalies (TWSA) in the Three Gorges Reservoir Area (TGRA) over two decades, from 2003 to 2023. The analysis utilizes data from the Gravity Recovery and Climate Experiment (GRACE) and its successor mission (GRACE-FO), complemented by Global Land Data Assimilation System (GLDAS) models and ECMWF Reanalysis v5 (ERA5) datasets. The research methodically explores the comparative contributions of natural factors and human activities to the region’s hydrological dynamics. By integrating the GRACE Drought Severity Index (GRACE-DSI), this study uncovers the dynamics of droughts during extreme climate events. It also reveals the pivotal role of the Three Gorges Dam (TGD) in mitigating these events and managing regional water resources. Our findings indicate a notable upward trend in TWSA within the TGRA, with an annual increase of 0.93 cm/year. This trend is largely due to the effective regulatory operations of TGD. The dam effectively balances the seasonal distribution of water storage between summer and winter and substantially reduces the adverse effects of extreme droughts on regional water resources. Further, the GRACE-DSI analysis underscores the swift recovery of TWSA following the 2022 drought, highlighting TGD’s critical role in responding to extreme climatic conditions. Through correlation analysis, it was found that compared with natural factors (correlation 0.62), human activities (correlation 0.91) exhibit a higher relative contribution to TWSA variability. The human-induced contributions were derived from the difference between GRACE and GLDAS datasets, capturing the combined effects of all human activities, including the operations of the TGD, agricultural irrigation, and urbanization. However, the TGD serves as a key regulatory facility that significantly influences regional water resource dynamics, particularly in mitigating extreme climatic events. This study provides a scientific basis for water resource management in the TGRA and similar large reservoir regions, emphasizing the necessity of integrating the interactions between human activities and natural factors in basin management strategies.